On embedding degree sequences - Csaba, Béla; Vásárhelyi, Bálint Márk (Informatica, 2019)
Assume that we are given two graphic sequences, π_1 and π_2. We consider conditions for π_1 and π_2 which guarantee that there exists a simple graph G_2 realizing π_2 such that G_2 is the subgraph of any simple graph G_1 that realizes π_1.